2011
DOI: 10.1539/joh.10-0032-oa
|View full text |Cite
|
Sign up to set email alerts
|

Association between Job Stress and Insomnia in Korean Workers

Abstract: Association between Job Stress and Insomnia in Korean Workers: Hwan-Cheol Kim, et al.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
71
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(85 citation statements)
references
References 43 publications
(47 reference statements)
8
71
0
Order By: Relevance
“…Previous studies (Eriksen et al 2008;Fahlen et al 2006;Kim et al 2011;Kudielka et al 2004) showed a significant association between low reward and various sleep outcomes; only one of these studies had a prospective design (Eriksen et al 2008). Job insecurity was associated with sleep problems in model 1 in our cross-sectional analysis.…”
Section: Comparison With the Literaturementioning
confidence: 56%
See 3 more Smart Citations
“…Previous studies (Eriksen et al 2008;Fahlen et al 2006;Kim et al 2011;Kudielka et al 2004) showed a significant association between low reward and various sleep outcomes; only one of these studies had a prospective design (Eriksen et al 2008). Job insecurity was associated with sleep problems in model 1 in our cross-sectional analysis.…”
Section: Comparison With the Literaturementioning
confidence: 56%
“…Job insecurity was associated with sleep problems in model 1 in our cross-sectional analysis. Two previous studies reported an association between job insecurity and sleep outcomes in cross-sectional samples of Korean workers (Kim et al 2011;Park et al 2013).…”
Section: Comparison With the Literaturementioning
confidence: 95%
See 2 more Smart Citations
“…Workers who have a sleep disorder such as insomnia or OSAS have reported higher job stress compared with that of healthy individuals [16]. Å´kerstedt et al [17] argue that sleep may be involved in the development of burnout, as individuals with symptoms of burnout also report sleep fragmentation.…”
Section: Introductionmentioning
confidence: 99%